Kennesaw : Natural History of a Southern Mountain - Graham, Sean P. (Book collections on Project MUSE., 2021)
"Combining a summary of the park's history with an in-depth introduction to Kennesaw Mountain's geology, forest ecology, wildlife, and role in global bird migration, "Kennesaw: Natural History of a Southern Mountain" is the first in-depth ecological treatment of one of the most frequently visited National Battlefield parks in the country"--